Characterization of the parameters of interior permanent magnet synchronous motors for a loss model algorithm. (August 2017) - Caruso, M.; Di Tommaso, A.O.; Miceli, R.; Nevoloso, C.; Spataro, C.; Viola, F.
Highlights: Characterization of the parameters of interior permanent magnet synchronous motors. Identification of real-time control algorithm for efficiency enhancement of IPMSMs. Analysis on the optimized magnetization condition for power losses minimization. Abstract: The paper provides the results of a detailed experimental study on the variations of the characteristics of an interior permanent magnet synchronous motor, when load, speed and/or magnetization conditions vary. In particular, the characterization is carried out by assessing, for several working conditions, the motor parameters that influence its efficiency. From the knowledge of the variability of these parameters, it is possible to develop a dynamic model of the motor, which accurately describes its behaviour and allows estimating the power losses for whatever speed and load. In order to validate the model, the values of the power losses obtained by using the model are compared with the values measured with experimental tests. The study shows that it is possible to maximize the motor efficiency just acting on the direct axis current component and, therefore, it can be considered a first step towards the definition of a loss model algorithm for a control drive system able to minimize in real-time the power losses of the motor.